A review of shape memory material's applications in the offshore oil and gas industry. (9th August 2017) - Patil, Devendra; Song, Gangbing
Abstract: The continuously increasing demand for oil and gas and the depleting number of new large reservoir discoveries have made it necessary for the oil and gas industry to investigate and design new, improved technologies that unlock new sources of energy and squeeze more from existing resources. Shape memory materials (SMM), with their remarkable properties such as the shape memory effect (SME), corrosion resistance, and superelasticity have shown great potential to meet these demands by significantly improving the functionality and durability of offshore systems. Shape memory alloy (SMA) and shape memory polymer (SMP) are two types of most commonly used SMM's and are ideally suited for use over a range of robust engineering applications found within the oil and gas industry, such as deepwater actuators, valves, underwater connectors, seals, self-torqueing fasteners and sand management. The potential high strain and high force output of the SME of SMA can be harnessed to create a lightweight, solid state alternative to conventional hydraulic, pneumatic or motor based actuator systems. The phase transformation property enables the SMA to withstand erosive stresses, which is useful for minimizing the effect of erosion often experienced by downhole devices. The superelasticity of the SMA provides good energy dissipation, and can overcome the various defects and limitations suffered by conventional passive damping methods. The higher strain recovery during SME makes SMP ideal for developments of packers and sand management in downhole. The increasing number of SMM related research papers and patents from oil and gas industry indicate the growing research interest of the industry to implement SMM in offshore applications. This paper reviews the recent developments and applications of SMM in the offshore oil and gas industry.